Development of Electronic Teaching Material Containing South Kalimantan’s Traditional Game to Improving Students’ Problem-Solving Ability - Adindha Maidiana Ariyanti; Zainuddin Zainuddin; Dewi Dewantara (Universitas Muhammadiyah Purworejo, 2022)
The low problem-solving skills of students and the lack of ability of students to apply the physics concepts they have learned in real life have encouraged researchers to develop electronic teaching materials containing traditional South Kalimantan games. This research is expected to be able to obtain valid, practical, and effective electronic teaching materials so that they are feasible and can be applied in training students' problem-solving skills. This study uses the ADDIE model and includes the type of research and development (R&D). The development was carried out in a field test at SMA N 6 Banjarmasin. Data collection is done using validation instruments, learning implementation sheets, and learning outcomes tests that are combined with problem-solving skills. The data were analyzed by quantitative descriptive analysis where the results obtained showed that: (1) electronic teaching materials containing traditional games obtained valid categories (2) electronic teaching materials including practical based on the assessment of the implementation of the lesson plan meet the practical category; and (3) the electronic teaching materials developed are also effective because n-gain of 0.78 is in the high category. Thus, electronic teaching materials containing traditional games developed are feasible to train students' solving skills in learning physics.